PENGARUH BOPO, NPL, NIM DAN CAR TERHADAP KINERJA KEUANGAN BANK (STUDI PADA BANK-BANK YANG LISTED DI BURSA EFEK INDONESIA) - Bambang Sudiyatno; Rini Setiyowati (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
The purpose of this study is to analyze the influence of BOPO, NPL, NIM and CAR on thefinancial performance of banks listed on the Indonesia Stock Exchange in the period 2006 to 2009.Samples were taken based on purposive sampling of 28 banking companies with the followingcriteria: the company issued financial statements for four consecutive years ie 2006 to 2009. Thetype of data used are secondary data and data collection methods through technicaldocumentation. Analysis technique used is normality test, the classical assumption, and multiplelinear regression based on the merging of data time series and cross section called the polleddata. The results showed that variables significantly and negatively related BOPO against thebank's financial performance, the NPL variable has negative and significant impact on thefinancial performance of banks, NIM variable has positive and significant impact on the financialperformance of banks and CAR does not affect the bank's financial performance. The ability of thebank's financial performance could be explained by variables BOPO, NPL, NIM and the CAR of97.5%, Sebagimana shown by the Adjusted R-Square of 0.975. The remaining 2.5% is explained byother factors outside the model.Key Words: BOPO, Non-Performing Loans, Net Interest Margin, Capital Adequacy Ratio and thebank's financial performance.